Molecular characterization of intervening sequences in 23S rRNA genes and 23S rRNA fragmentation in Taylorella equigenitalis - Tazumi, A; Sekizuka, T; Moore, J E; Millar, B C; Taneike, I; Matsuda, M (Folia microbiologica, 2008)
Using two primer pairs constructed in silico for the amplification of the intervening sequences (IVSs) of the 23S rRNA gene sequences of the genus Taylorella, none of the three representative T. equigenitalis strains NCTC11184(T), Kentucky 188 and EQ59 was shown to contain any IVSs in the first quarter region. In the central region, all three strains possessed one approximately 70 bp IVS (TeIVS2) different from any IVSs found in T. asinigenitalis. The predicted secondary structure model of the IVSs contained stem and loop structures. The central region of the IVS-stem structure contains an identical double-stranded consensus 15-bp sequence. The purified RNA fraction from the three strains contained 16S and 4-5S RNA species but no 23S rRNA species. Thus, the primary 23S rRNA transcripts from the three strains would be cleaved into approximately 1.2- and 1.6-kb rRNA fragments and approximately 70-bp IVS. In addition, 16 other T. equigenitalis isolates were found to carry a similar 70-bp IVS in the central region and to produce fragmented 23S rRNA.
Keywords: bakteriální RNA; druhová specificita; sekvence nukleotidů; RNA, Ribosomal, 23S; Sequence Homology, Nucleic Acid; Nucleic Acid Conformation; Gram-Negative Bacterial Infections; Consensus Sequence; RNA Processing, Post-Transcriptional; posttranskripční úpravy RNA; molekulární sekvence - údaje; sekvenční homologie nukleových kyselin; sekvenční seřazení; Species Specificity; nemoci koní; RNA ribozomální 23S; Introns; konformace nukleové kyseliny; introny; Animals; Genes, Bacterial; konsenzuální sekvence; zvířata; gramnegativní bakteriální infekce; Horses; koně; Molecular Sequence Data; Base Sequence; RNA, Bacterial; Horse Diseases; bakteriální geny; Sequence Alignment; Taylorella equigenitalis